Family values in university students - Quezada Zevallos, Jenny (2001)
A comparative descriptive study was made of a set of university students both boys and girls. The study showed that the main coming from then parents are: respect for others, dignity, justice, personal development, emancipation, familiar security and sincere friendship. These standards are the same they will expect to teach their children because these are the most important ones in life. them. The child entering adolescence will assume the standards given by his parents and use them as the most important thing in his life, the same he will teach to his/her children.